Factors Influencing the Adoption of Management Accounting in Nepal’s Co-operatives - Khatiwada, Atmaram (KMC Journal, 2026)
The management accounting is deliberative to decision-making, long-term planning and long-term sustainability of co-operatives run on the values of supportive and democratic governance. Despite the growing importance of financial management, the adoption of management accounting within Nepalese cooperatives remains under-researched, particularly regarding the interplay between organizational, technological, and environmental factors. This study adopts quantitative framework by using descriptive research design and causal-comparative research design to question the identified determinants. Ten cooperatives - savings and credit, multipurpose and dairy cooperatives - located in Prashuram Municipality were the target of the investigation. The data was collected by using structured questionnaire that was sent to a sample of 112 respondents, including the board members, the management employees, and the general members. The SPSS was used to analyze the data that incorporated the use of descriptive statistics, correlation analysis, and regression analysis. The results show that technological aspects (r = 0.65), organizational aspects (r = 0.62), rivalry (r = 0.60) and environmental aspects (r = 0.58) are positively and significantly related to management accounting adoption. The results of multiple regressions suggest that these predictors reveal 61 percent of variance in management accounting adoption (R2 = 0.61), and there are no problems with multicollinearity or autocorrelation. The study notes that technology and organizational support are the main drivers for competitive and environmental pressures. The practical implications of this paper propose that to enhance the leadership, increase capacity, to refine decision-making processes and enhance the financial performance, the management accounting must be used by the cooperative boards, policymakers and training institutions to promote the sustainable development of the cooperatives in Nepal.